The influence of a translucent fiberglass post on the polymerization of dual cure resin cement analyzed by electron paramagnetic resonance - Salomão, Fabio Martins [UNESP]; Vicentin, Bruno Luiz Santana; Contreras, Edwin Fernando Ruiz; Hoeppner, Márcio Grama; Di Mauro, Eduardo (FapUNIFESP (SciELO), 2015)
Electron Paramagnetic Resonance (EPR) was used as an alternative method to study the conversion degree of dual cure resin cement and verify the influence of prefabricated translucent fiberglass post on the dual cure resin cement polymerization at different restoration points. The post cementation of White Post DC (FGM, Joinville, SC, Brasil) was simulated using the dual cured resin cement Allcem (FGM, Joinville, SC, Brasil) in three different protocols: cement irradiated for 40 s; no light irradiation and cement irradiated with sealed cementation line. 2mm samples were obtained from three post sections and EPR spectra were obtained 10 minutes and 24 hours after mixing the base paste and catalyst of the cement. Results shows that the light curing protocol influenced the concentration of free radicals up to 8mm of the restoration, and the capacity of light transmission of the post was significant for the first 8mm of restoration and is non-existent in the deepest points of a simulated root canal. The cure in the apical part of restoration is exclusively chemical.
Keywords: EPR; Free radical; Light transmission; Photopolymerization; Self-cure